Melanoma‐derived extracellular vesicles instigate proinflammatory signaling in the metastatic microenvironment. Issue 9 (4th July 2019) - Gener Lahav, Tzlil; Adler, Omer; Zait, Yael; Shani, Ophir; Amer, Malak; Doron, Hila; Abramovitz, Lilach; Yofe, Ido; Cohen, Noam; Erez, Neta
Abstract : The major cause of melanoma mortality is metastasis to distant organs, including lungs and brain. Reciprocal interactions of metastasizing tumor cells with stromal cells in secondary sites play a critical role in all stages of tumorigenesis and metastasis. Changes in the metastatic microenvironment were shown to precede clinically relevant metastases, and may occur prior to the arrival of disseminated tumor cells to the distant organ, thus creating a hospitable "premetastatic niche." Exosomes secreted by tumor cells were demonstrated to play an important role in the preparation of a hospitable metastatic niche. However, the functional role of melanoma‐derived exosomes on metastatic niche formation, and the downstream pathways activated in stromal cells at the metastatic niche are largely unresolved. Here we show that extracellular vesicles (EVs) secreted by metastatic melanoma cells that spontaneously metastasize to lungs and to brain, activate proinflammatory signaling in lung fibroblasts and in astrocytes. Interestingly, unlike paracrine signaling by melanoma cells, EVs secreted by metastatic melanoma cells instigated a proinflammatory gene signature in lung fibroblasts but did not activate wound‐healing functions, suggesting that tumor cell‐secreted EVs activate distinct CAF characteristics and tumor‐promoting functions. Moreover, melanoma‐secreted EVs also activated proinflammatory signaling in astrocytes, indicating that EV‐mediated reprogramming of stromal cells is a general mechanism of modulating the metastatic niche in multiple distant organs. Thus, our study demonstrates that melanoma‐derived EVs reprogram tumor‐promoting functions in stromal cells in a distinct manner, implicating a central role for tumor‐derived EV signaling in promoting the formation of an inflammatory metastatic niche. Abstract : What's new? Malignant melanoma cells rapidly colonize distant organs but the mechanisms that allow interactions with the metastatic microenvironment remain largely unknown. Here the authors show that melanoma‐derived extracellular vesicles modify the stroma of distant organs and contribute to the formation of a hospitable metastatic microenvironment. Specifically, extracellular vesicles activate pro‐inflammatory signaling in fibroblasts and in astrocytes, contributing to instigation of tumor‐promoting inflammation at the metastatic microenvironment of lungs and brain.